The Relationship Between Nurses’ Knowledge of Infection Prevention and Hand Hygiene Compliance: A Health Belief Model Approach at Oe-Kussi Referral Hospital - Manuela Monalisa Lindalva Pui; Gipta Galih Widodo (Borneo Nursing Journal (BNJ), 2026)
Background: Healthcare-associated infections remain a major patient safety concern, and inadequate hand hygiene contributes to their transmission. Nurses’ knowledge of infection prevention may influence risk perceptions and adherence to hand hygiene practices. Research Objective: This study examined the relationship between nurses’ knowledge of infection prevention and hand hygiene compliance using the Health Belief Model as a conceptual framework at Oe-Kussi Referral Hospital. Methods: A quantitative cross-sectional correlational study was conducted among 30 registered nurses selected through purposive sampling. Knowledge was assessed using a structured questionnaire, whereas hand hygiene compliance was measured through direct observation using a checklist based on World Health Organization recommendations. Data were analyzed using descriptive statistics, the Chi-square test, and Spearman rank correlation, with statistical significance set at p<0.05. Results: Twenty-five nurses (83.3%) had good knowledge of infection prevention, and 20 nurses (66.7%) were compliant with hand hygiene practices. Knowledge level was significantly associated with hand hygiene compliance (p=0.012). A strong positive correlation was also identified between knowledge and compliance (r=0.62; p<0.001). Conclusion: Better knowledge of infection prevention was significantly associated with higher hand hygiene compliance among nurses at Oe-Kussi Referral Hospital. Continuing education should be supported by regular monitoring and organizational measures to promote consistent adherence to hand hygiene practices.